(untitled) (Res Medica, 2013)
From a dissertation to the Society on 18th October, 1963. There is a note in a paper written in 1943 by Kritchley which mentions that after a ship had been torpedoed in an area where the water was 29°F , only one man out of a crew of ten survived longer than half an hour in the water. Losses during the war resulting from cold immersion were catastrophic, accounting for perhaps two-thirds of the people who lost their lives at sea. In 1945 this question was reviewed by Molnar. He collected a number of records of incidents involving immersion in cold water from the files of the Bureau of Medicine and Surgery U.S. Navy, Washington, He chose those records which included the temperature of the water, or an accounted note of the date and locality so that the temperature could be read off from maps, and some indication of the duration of immersion.